Logic-signal-based multiplex detection of MiRNAs with high tension hybridization and multiple signal amplification. Issue 12 (13th May 2020) - Tang, Yaqin; He, Xiao; Yuan, Rui; Liu, Xingming; Zhao, Yi; Wang, Tingting; Chen, Hui; Feng, Xuli
Abstract : A multiplex miRNA detection scheme with simultaneous multiple signal output by single excitation has been reported. Abstract : MicroRNAs (miRNAs) are crucial regulators of gene expression. The abnormal expression of miRNA is often closely related to many diseases. However, the accurate clinical profiling of miRNA expression remains a great challenge due to the high similarity and wide variety of miRNA sequence structures. Here, we report a highly specific and sensitive multiplex miRNA detection scheme with high tension hybridization and dual signal amplification based on the recyclable autocatalytic DNAzyme and a light harvesting conjugated polymer. Multiple signals can be read out simultaneously by single excitation through the efficient multiple fluorescence resonance energy transfer (FRET) between the conjugated polymer and different small molecule dyes. In addition, different types of logic gates can also be operated by observing the emission intensities of the labeling dyes with miRNAs as inputs, thus giving rise to a new way for the specific detection of certain miRNAs according to the logic signals. Furthermore, we successfully applied the strategy for multiple miRNA detection in cell lysates and the results agree well with those of qRT-PCR. Thus, we believe that this platform holds great potential for miRNA detection in biological samples.